METHOD FOR SELECTING AND TECHNICAL ASPECTS OF SURGICAL TREATMENT FOR INFECTED PANCREATIC NECROSIS IN PATIENTS WITH DIABETES MELLITUS - N.A. Kasimov; D.M. Khakimov; G.M Khojimatov; Kh.Kh Khamdamov (Journal of modern medicine, 2026)
The scientific article presents methods and technical techniques for choosing surgical tactics for infected pancreatic necrosis (IPN) in patients with diabetes mellitus (DM). Clinical trials were conducted on 188 patients with IPN who underwent treatment at the RSCEMP AB between 2012 and 2025. Depending on the period and presence of DM, all included patients were divided into 3 groups. The control group consisted of 62 (33%) patients with IPN against the background of DM who underwent treatment in 2012-2018, while the comparison group was represented by 62 (33%) patients with IPN without DM. The main group included 64 (34%) patients with IPN against the background of diabetes mellitus who underwent treatment between 2019 and 2025, which was based on a structured assessment of the process's severity and the sequential selection of surgical tactics. The research results showed that the developed differentiated surgical techniques based on limited necrectomy, stage-by-stage removal of necrotic masses, and gentle drainage ensure a more favorable course of the postoperative period and a reduction in the frequency of local purulent-septic complications and repeated surgical interventions.